Pengaruh Penerapan Good Corporate Governance dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Properti dam Real Estate Yang Terdaftar Di BEI Periode 2020-2022 - Wafiq Nurul Azizah; Enny Arita (CV. ITTC INDONESIA, 2024)
This research aimed to examine the effect of goost corporate governance that was referred to as managerial oumership, institutional oumership, independent commissioner board, and capital structur which seas referred to as deht to equity ratio (DER); on the firm value was referred to price to book value (PSV) The population was 85 property sector companies and real estate with purposive sampling as the data collection technique in line with that, there were 24 data samples with 3 years of observation (2020-2022) Furthermore, the data used were secondary, in form of companies annual reports, that were list on the indonesia stock exchange (IDX) during 2016-2020. The data analysis technique used descriptive statistics and multiple linear regression with SPSS. The result concluded that on inumagerial ownership and institusional oumership had a positive effect on firm value. However, independent commissioner board, as well as a capital structure (DER), had a significant negative effect on firm value.